Gene polymorphism associated with endothelial nitric oxide synthase (4VNTR, G894T, C786T) and unexplained recurrent spontaneous abortion risk: A meta-analysis. Issue 4 (January 2019) - Zhao, Xiaoxuan; Li, Qiang; Yu, Feifei; Lin, Lina; Yin, Wenqing; Li, Jiawei; Feng, Xiaoling
Abstract : Abstract: To evaluate the association between endothelial nitric oxide synthase gene polymorphisms (4VNTR A/B, G894T, C786T) and risk of URSA. Related case-control studies were collected by computers. A meta-analysis was conducted using Stata 12.0 software to assess the strength of association. Altogether 37 articles were examining the relationship between endothelial nitric oxide synthase gene polymorphisms and URSA, among which sixteen (16) studies were related to 4VNTR, twelve (12) to G894T, and nine (9) to C786T, the study suggested that 4VNTR A/B polymorphism was closely connected with URSA risk under all gene models except for recessive model (AA vs. BB + AB). The integrated result which indicated the association between G894T gene mutation and URSA risk had been shown under homozygote (TT vs. GG; OR 1.585, 95%CI 1.175–2.138) and recessive models (TT vs. TG + GG; OR 1.530, 95%CI 1.142–2.052). Considering heterogeneity in the remaining gene models, subgroup analysis was performed on ethnicity, and the results showed that it was the dominant (TT + TG vs. GG; OR 1.585, 95%CI 1.175–2.138) and additive models (T vs. G; OR 1.727, 95%CI 1.372–2.175) of G894T in Asians and the heterozygote model (TG vs. GG; OR 1.015, 95%CI 0.846–1.217) in Caucasians that were associated with URSA ( P < .05). Besides C786T gene was significantly connected with URSA under all models except for additive model (T vs. C). It is of great guiding significance for screening out and preventing URSA among high-risk women via testing on 4VNTR A/B, G894T, C786T eNOS under gene models mentioned above which are closely associated with URSA.